2007
DOI: 10.1111/j.1365-2133.2006.07703.x
|View full text |Cite
|
Sign up to set email alerts
|

Galli?Galli disease is an acantholytic variant of Dowling?Degos disease

Abstract: Dowling-Degos disease (DDD; MIM 179850) is a rare autosomal dominant disorder characterized by reticulate flexural hyperpigmentation associated with hyperkeratotic papules, pitted perioral scars and comedo-like lesions or cysts. 1 Characteristic histopathological features include filiform epithelial downgrowths of the rete ridges, typically involving the follicular infundibulum, basilar hyperpigmentation and dermal melanosis. Follicular retention cysts and perivascular mononuclear infiltrates can also be prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 18 publications
1
45
1
6
Order By: Relevance
“…Recently, a mutation which is predicted to disrupt the KRT5 initiation codon leading either to haploinsuYciency or the synthesis of a N-deleted K5 mutant protein has been reported in a patient with Galli-Galli disease (Sprecher et al 2007). Since the same mutation (p.Ile140 fs) has been reported both in Galli-Galli disease and in DDD (Betz et al 2006;Sprecher et al 2007), Galli-Galli disease seems to be merely a variant of DDD.…”
Section: Dowling Degos Diseasementioning
confidence: 99%
“…Recently, a mutation which is predicted to disrupt the KRT5 initiation codon leading either to haploinsuYciency or the synthesis of a N-deleted K5 mutant protein has been reported in a patient with Galli-Galli disease (Sprecher et al 2007). Since the same mutation (p.Ile140 fs) has been reported both in Galli-Galli disease and in DDD (Betz et al 2006;Sprecher et al 2007), Galli-Galli disease seems to be merely a variant of DDD.…”
Section: Dowling Degos Diseasementioning
confidence: 99%
“…The acantholytic variant of Dowling-Degos disease is called Galli-Galli disease [48]. These two entities are caused by mutations in the keratin 5 gene (KRT5) [48]. By correlating genotype-phenotype Hanneken et al [49] found that patients with the KRT5 mutation c.418dupA presented reticular hyperpigmentation in the flexural areas, whereas in patients with a more disseminated pattern consisting of hyperpigmented lentiginous maculae this mutation could not be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…This is said to be more prominent in Dowling-Degos disease; in acropigmentation of Kitamura only a slight epidermal atrophy is present. The acantholytic variant of Dowling-Degos disease is called Galli-Galli disease [48]. These two entities are caused by mutations in the keratin 5 gene (KRT5) [48].…”
Section: Discussionmentioning
confidence: 99%
“…The only disease which has unambiguous diagnostic criteria is DDD, with its specific genetic changes. Galli-Galli disease resembles DDD but reveals basal layer acantholysis upon histologic examination [11,12]; keratin mutations are found but presumably involve a region of the molecule which is essential to cell-cell adherence [13]. One could speculate that Galli-Galli disease lies somewhere between DDD and EBS with mottled hyperpigmentation.…”
Section: Discussionmentioning
confidence: 99%